Mesa-assisted VLS Growth of GaAs Nanowires - Roumeliotis, Michael (My University, 2008)
Periodic arrays of Au patterns (dots and lines) were produced via electron beam lithography (EBL). GaAs mesas were produced by using the Au structures as a mask and wet etching the GaAs (lll)B substrates, leaving Au resting above GaAs pillars. Annealing experiments at typical nanowire growth temperatures (550°C) were performed on both mesa-supported samples and a control sample without mesas, and were later characterized by scanning electron microscopy (SEM). From SEM images, a model is proposed to describe the evolution of the Au seed particle during exposure to typical growth conditions. The Au particle is subject to not only a melting process but is also modified by a volume increase due to incorporating Ga atoms and a subsequent crystal structure change. Palpable discrepancies between the mesa-supported and control samples were observed after annealing experiments, suggesting the mesas were effective in confining the migration of the Au. NW s were then grown via gas source molecular beam epitaxy (GS-MBE). Discemable variation amongst the results was evident when a comparison between annealed samples and the grown counterpart was made. The inconsistency is ascribed to the NW growth process beginning only after supersaturation at the growth interface. This saturation took place only after 2-D film growth on the substrate surpassed the height of the mesas rendering the structures less functional.
Keywords: VLS; GaAs; nanowires; Periodic arrays